InShot Application Training: A Practical Solution for PPG UKIN Preparation - Fadlilah, Fadlilah; Syefrinando, Boby; Sanjaya, Budi; Chaniago, Fransisko; Ramli, Michrun Nisa; Bangsawan, Indra; Fitriani, Suci; Habibi, M. Fadly; Hamdan, Hamdan (Lembaga Dongan Dosen, 2025)
Performance Test (UKIN) is a mandatory requirement for teachers participating in the PPG program, which involves planning, implementing, and evaluating learning activities according to lesson plans (RPP) for the subjects they teach, utilizing digital-based learning media. Therefore, thorough preparation is essential before teachers in the PPG program take the Performance Test (UKIN). The purpose of this community service activity is to equip teachers participating in the PPG program to face the Performance Test (UKIN) at the Faculty of Tarbiyah and Teacher Training, UIN Sulthan Thaha Saifuddin Jambi. This training activity employs the Asset Based Community Development (ABCD) approach. This approach serves as the strategy used in the training, targeting PPG program teachers as participants who inherently possess pedagogical competence, teaching experience, and smartphones as their assets. The results of this community service indicate that participants were able to understand how to use the InShot application as a medium for creating teaching videos. Participants not only learned the basic features of the InShot application but were also able to practice video editing, including cutting, adding text, audio, transitions, and saving the final output. Therefore, this training directly contributes to improving the readiness of PPG teachers in facing the Performance Test (UKIN).